KARAKTERISTIK ENKAPSULAT MINYAK SAWIT MERAH DENGAN PENGAYAAN Î²-KAROTEN - YULIASARI, Shannora; Fardiaz, Dedi; Andarwulan, Nuri; Yuliani, Sri (Informatika Pertanian, 2016)
This study aimed to evaluate the effect of maltodextrin combination with different encapsulation materials in the encapsulation of red palm oil by spray drying, in order to maximize encapsulation efficiency and retention of Î²-carotene. Maltodextrin was combined with xanthan gum (XG), gum arabic (GA), sodium caseinate (SC). The study was designed using a block randomized design with ten treatments and three replicates. The use of different combinations of encapsulation materials in this study had a significant effect (p<0.05) on the characteristic of encapsulates. The best encapsulation efficiency and Î²-carotene retention were obtained with MD:XG at a combination of 99.7:0.3%, while the lowest encapsulation efficiency and Î²-carotene retention were obtained for MD:SC. Combination of MD:XG produced encapsulate with 1.03% of surface oil, 92.40% of oil retention, 72.05% of encapsulation efficiency, and 72.65% of Î²-caroten retention. The mixtures of different encapsulation materials influenced encapsulate morphology. The MD:SC encapsulate had higher dents and folds on encapsulate surface, whereas the combination of MD:XG resulted in a smoother surface of the encapsulate.